Meningkatkan Kinerja Bisnis Lumpia Semarang Melalui Keunggulan Bersaing - Bogy Febriatmoko; Widhian Hardiyanti; Sartika Wulandari (Jurnal Bisnis dan Ekonomi, 2019)
This research was conducted on small and medium business. This research takes an object on the typical food Lumpia in Semarang. This research is a continuation of our previous research on Semarang's specialty foods, specifically more specifically researching the lumpia and want to increase the competitive advantage of the product in Semarang, so that the product can continue to exist and develop as Semarang's special food.The purpose of this research is to identify the problems that arise related to competitive advantage, the performance of UMKM lumpia business in Semarang, and to know whether competitive advantage can be a bridge between product innovation with business performance & between market orientation and business performance. In addition to know the effect of product innovation & market orientation on business performance.The population of this research is lumpia industry in Semarang city which amounted to 30, with the method of collecting data in the form of questionnaire obtained from businessman lumpia as respondent. Stages in this research are as follows: identification of research problems, data collection and tabulation, data quality test and data analysis. The result of this study are, the effect of market orientation (OP) on competitive advantage (KB) is significantly positive. While the influence of OP on business performance (KIB) is postitf, but not significant.